Microsporogênese em Brachiaria brizantha (Poaceae) : análise de acessos poliplóides - Santos, Elisangela Mendes dos (2009)
Brachiaria brizantha is one of the most promising Brachiaria species and is the best represented in the Brachiaria germplasm collection available at Embrapa Beef Cattle. Accessions of this species are under evaluation not only for the production of new cultivars but also to be used for interspecific hybridization. However, only tetraploid accessions (2n=36) with high meiotic stability can be used as pollen donors in crosses. Thus, the objective of this research was to determine the chromosome number, the ploidy level and the meiotic behavior, through conventional methodology, of some accessions of this species as a subsidy to the breeding program underway at Embrapa Beef Cattle. Among the 17 accessions analyzed, 13 were tetraploid (2n=36), two, pentaploid (2n=45), and two, hexaploid (2n=54), all derived from x=9. Meiotic abnormalities were recorded in all the accessions, but in variable frequencies. Abnormalities typical of polyploids, such as precocious chromosome migration to the poles and laggard chromosomes leading to micronuclei formation were the most common, but cell fusion, cytomixis, chromosome stickiness and irregular cytokinesis were also recorded among accessions. All the abnormalities recorded compromise pollen viability. Thus, among the accessions analyzed, some of them, by presenting low frequency of meiotic abnormalities, could be indicated to act as pollen donor in intra or interspecific crosses in the Brachiaria breeding program.